1992
DOI: 10.1210/jcem.75.4.1400863
|View full text |Cite
|
Sign up to set email alerts
|

Long-term longitudinal measurements of plasma dehydroepiandrosterone sulfate in normal men.

Abstract: Dehydroepiandrosterone sulfate (DS) was measured by direct tritium RIA in longitudinal plasma specimens from 97 normal healthy male participants in the Baltimore Longitudinal Study of Aging. Fasting blood was collected at regular visits (approximately 1.5 yr apart) over an average 13 yr of adulthood (cumulative age range: 32-83 yr). DS was measured in 3-4 widely spaced specimens from each subject. A decline in DS was found in 65 (67%) subjects, 13 subjects (13%) showed no change, and increases were found in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
178
2
7

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(200 citation statements)
references
References 1 publication
13
178
2
7
Order By: Relevance
“…However, differences between responders and nonresponders in cortisol/DHEAS ratios revealed an association with age of onset. These findings are supported by investigations that reported that age and DHEA(S) concentrations are inversely correlated (Orentreich et al, 1992;Binello and Gordon, 2003;Ritsner et al, 2004).…”
Section: Commentsupporting
confidence: 74%
“…However, differences between responders and nonresponders in cortisol/DHEAS ratios revealed an association with age of onset. These findings are supported by investigations that reported that age and DHEA(S) concentrations are inversely correlated (Orentreich et al, 1992;Binello and Gordon, 2003;Ritsner et al, 2004).…”
Section: Commentsupporting
confidence: 74%
“…DHEA and it's sulfated form, DHEAS, are present in adult men and women at serum levels 100 to 500 times higher than those of testosterone and 1000 to 10,000 times higher than those of estradiol but levels decrease up to 80% with age [1,14,15]. DHEA is widely used as an overthe-counter dietary supplement with unsubstantiated claims of beneficial effects on body composition, cardiometabolic, immune, and neurobiological functions [16] as well as uncertain long-term safety.…”
Section: Discussionmentioning
confidence: 99%
“…1b, f;Plymate et al, 1989;Feldman et al 2002;Luboshitzky et al 2003;Garyfallou et al 2005;Kaufman and Vermeulen 2005;Page et al 2007;Schlatt et al 2008;Bremner 2010), and an even more pronounced attenuation of their 24-h DHEAS rhythm (Figs. 1d, h;Orentreich et al 1992;Labrie et al 1997;Wise 1999;Urbanski et al 2004;Downs et al 2008). An age-related decline has also been observed for leptin in old male rhesus macaques (data not shown; Downs and Urbanski 2006a).…”
Section: Age-related Endocrine Changesmentioning
confidence: 99%